Climate Changes and Dynamics of the Ecological Niche of Threatened Woody Species in the Dahomey Gap Corridor in Benin - Chabi, Romeo Brice Kolawole; Dossou, Etienne; Yabi, Biaou Francis; YABI, IBOURAÏMA; TENTE, AGOSSOU BRICE HUGUES (My University, 2021)
In Benin, the southern part is devoid of continuous dense humid forest like the Ivory Coast or Nigeria due to the presence of Dahomey Gap or Dahomey gap or aridness corridor. But the meager natural resources of this already fragile environment are affected by the effects of environmental changes, particularly climatic ones. The present research aims to analyze the dynamics of the distribution areas of endangered woody species under the effect of climate change in the part affected by Dahomey-Gap in Benin. The methodology employed two approaches including phytosociological inventories and modeling based on the Maximum Entropy (MaxEnt) model on exposed woody species appearing in the IUCN international red list. Floristic inventories were carried out in 570 plots over an area of 30 m 30 m according to the Braun-Blanquet method within the different land use units that made it possible to analyze the floristic composition of the woody plants in the area of study. In total, 186 woody species have been identified in the Dahomey-gap in the southern part of Benin. Of these woody species, 17 are endangered. The endangered woody species (EN) are grouped in three (03) classes: Aphania senegalensis, Dalbergia setifera and Pterocarpus erinaceus. In addition, 10 woody species are vulnerable (VU) (Afzelia africana, Albizia ferruginea, Khaya senegalensis, Millettia warneckei, Nesogordonia papaverifera, Pierreodendron kerstingii, Pseudospondias microcarpa, Pterygota macrocarpa, Ricinodendron heudelotii and Vitellaria paradoxa). Finally almost 4 threatened woody species (Chrysophyllum albidum, Eucalyptus camaldulensis, Irvingia gabonensis and Milicia excelsa) are identified. Habitats distribution of 17 threatened woody species are found. The future projection by 2050 according to the optimistic RCP4.5 and pessimistic RCP8.5 emission scenarios revealed that these species could lose up to 35% of habitat area. Currently, the conditions are very favorable. These results should guide the management and conservation policies of woody resources in the area of study.
Keywords: Dahomey Gap (Benin); Woody Species; Conservation Status; Maximum Entropy (MaxEnt); Climatic Scenario